2021
DOI: 10.1016/j.genhosppsych.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety among front-line health-care workers supporting patients with COVID-19: A global survey

Abstract: Objective We aimed to explore anxiety status across a broad range of HCWs supporting patients with COVID-19 in different global regions. Method This was an international online survey in which participation was on voluntary basis and data were submitted via Google Drive, across a two-week period starting from March 18, 2020. The Beck Anxiety Inventory was used to quantify the level of anxiety. Results 1416 HCWs (70.8% medical doctors, 26.2% n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 28 publications
10
78
0
4
Order By: Relevance
“…The current study result is in concordance with recent studies of healthcare workers in German or Italy during COVID-19 that showed associations between working at COVID-19 frontline versus higher level of perceived stress or post-traumatic symptoms [44,49]. Further, other studies that examined mental health of medical professionals at frontline of COVID-19 pandemic also demonstrated increased odds of mental health worsening (depressive mood, anxiety, or burnout) in presence of working environments such as insufficient supply of personal protective equipment [50][51][52][53][54], endorsed barriers at working [55], increased physical and psychological workload [51,56,57], reduced amount of day-off and successive period of active duty after 24-h shifts [50]. Collectively, sufficient and timely supply of personal protective equipment and efficient distribution of rest period between the active duty are required for protection of mental health for PHDs at frontline of pandemic.…”
Section: Personal Protective Equipment Workhours At Screening Center and Mental Healthsupporting
confidence: 90%
“…The current study result is in concordance with recent studies of healthcare workers in German or Italy during COVID-19 that showed associations between working at COVID-19 frontline versus higher level of perceived stress or post-traumatic symptoms [44,49]. Further, other studies that examined mental health of medical professionals at frontline of COVID-19 pandemic also demonstrated increased odds of mental health worsening (depressive mood, anxiety, or burnout) in presence of working environments such as insufficient supply of personal protective equipment [50][51][52][53][54], endorsed barriers at working [55], increased physical and psychological workload [51,56,57], reduced amount of day-off and successive period of active duty after 24-h shifts [50]. Collectively, sufficient and timely supply of personal protective equipment and efficient distribution of rest period between the active duty are required for protection of mental health for PHDs at frontline of pandemic.…”
Section: Personal Protective Equipment Workhours At Screening Center and Mental Healthsupporting
confidence: 90%
“…Numerous multinational studies have already explored the prevalence of anxiety and depression during the pandemic and found a pooled prevalence of anxiety and depression varying widely from 11.6% to 58.9% and 16.1% and 69%, respectively [8][9][10][11][12][13][14][15][16][17][18][19][20]. However, none of these multinational studies had reported the prevalence and incidence of PTSD and panic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions could possibly affect their psychological well-being. It is expected that the current epidemic has placed significant stresses on people including HCWs, especially during the first outbreak when there was limited knowedge regarding its transmission, disease course, and pathogenesis (7) anxiety, and stress because of COVID-19 (8)(9)(10)(11). Previous studies has shown that many of the HCWs presented high levels of psychological distress during these outbreaks such as the severe acute respiratory syndrome (SARS) (12), H1N1 (13), and H7N9 (14) outbreaks.…”
Section: Introductionmentioning
confidence: 99%